2014
DOI: 10.1073/pnas.1410826111
|View full text |Cite
|
Sign up to set email alerts
|

Unusual kinetics of thermal decay of dim-light photoreceptors in vertebrate vision

Abstract: We present measurements of rate constants for thermal-induced reactions of the 11-cis retinyl chromophore in vertebrate visual pigment rhodopsin, a process that produces noise and limits the sensitivity of vision in dim light. At temperatures of 52.0-64.6°C, the rate constants fit well to an Arrhenius straight line with, however, an unexpectedly large activation energy of 114 ± 8 kcal/mol, which is much larger than the 60-kcal/mol photoactivation energy at 500 nm. Moreover, we obtain an unprecedentedly large p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 34 publications
6
41
2
Order By: Relevance
“…The energy threshold for G t activation by Rh6mr was similar to the Rh activation energy of 9.6 kcal/mol (Fig. 1B, black dashes) (20,21). These data suggest a similar mechanism of G t activation for both Rh6mr and Rh that involves opening of the opsin cytoplasmic side upon light illumination (22,23) and subsequent binding to G t .…”
Section: Significancesupporting
confidence: 62%
“…The energy threshold for G t activation by Rh6mr was similar to the Rh activation energy of 9.6 kcal/mol (Fig. 1B, black dashes) (20,21). These data suggest a similar mechanism of G t activation for both Rh6mr and Rh that involves opening of the opsin cytoplasmic side upon light illumination (22,23) and subsequent binding to G t .…”
Section: Significancesupporting
confidence: 62%
“…We found that the rate of the light-independent chromophore dissociation at 37 C was 2.2 Â 10 À7 s À1 , corresponding to a half-time of 36 days. This dissociation rate and the activation energy are distinct from the earlier biochemical data that measured the denaturation rate of Rho and opsin in vitro (8)(9)(10), and from the electrophysiological studies that measured thermal activation of single Rho molecules in native disc membranes (4,5). We conclude that the direct breaking of the PSB bond gave rise to the observed chromophore release.…”
Section: Introductioncontrasting
confidence: 57%
“…However, this value was derived from a single temperature, which makes comparison with other thermally activated processes difficult, and the experiments could not definitely distinguish between de novo pigment synthesis and chromophore exchange within the existing pigment. Moreover, all these in vivo data are at odds with the in vitro biochemical measurements, which found that the thermal decay rates of Rho at physiological temperature is on the order of 10 À6 s À1 (8,9). In our study, we revisited the stability of dark-state Rho by measuring the exchange rate of bound 11CR with free 9-cis-retinal (9CR) in Rho reconstituted into detergent/lipid bicelles.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations